2010
DOI: 10.1111/j.1432-2277.2010.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

The number of circulating recent thymic emigrants is severely reduced 1 year after a single dose of alemtuzumab in renal transplant recipients

Abstract: Summary To better understand the kinetics of the delayed reconstitution of peripheral CD4+ T‐cells after depletion with a single administration of alemtuzumab (AL) for renal transplantation, we evaluated in these patients the percentage and absolute number of recent thymic emigrants (RTEs) CD4+ T cells, together with naive and memory subsets, defined by the analysis of CD31, CD45RA and CCR7 expression, and compared with patients treated with a nondepleting protocol based on basiliximab, and with healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Whereas alemtuzumab efficiently depletes all CD52 + cells, the delayed reconstitution of CD4 + cells, resulting from deficient CD4 + cell homeostatic proliferation, susceptibility to apoptosis (28), and a relative expansion of immunoregulatory (29), which is even more prominent in MS patients (30), may also contribute to the prolonged CD4 + cell decrease and to the resetting of long-term CD4 + cell counts to numbers that are lower than at baseline (31).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas alemtuzumab efficiently depletes all CD52 + cells, the delayed reconstitution of CD4 + cells, resulting from deficient CD4 + cell homeostatic proliferation, susceptibility to apoptosis (28), and a relative expansion of immunoregulatory (29), which is even more prominent in MS patients (30), may also contribute to the prolonged CD4 + cell decrease and to the resetting of long-term CD4 + cell counts to numbers that are lower than at baseline (31).…”
Section: Discussionmentioning
confidence: 99%
“…This renders difficult to interpret the effects of thymic activity in the context of lymphopenia. In contrast, Scarsi et al (2010) reported a massive reduction of RTE one year post-transplantation after Campath-1H administration. This supports that naive CD4 + T cells −including RTE− may be highly sensitive to ATG (Louis et al, 2007;Gurkan et al, 2010)(see also below, paragraph §2.1.2) and that time is necessary for RTE "replenishment" after T cell depletion.…”
Section: The Role Of the Thymic Activity On Immune Reconstitution Aftmentioning
confidence: 90%
“…Whether data obtained with ATG can be transposed to Alemtuzumab remains to be determined. Nevertheless, few clinical studies are available regarding the CD4 + T cell lymphopenia induced by Alemtuzumab administration (Scarsi et al, 2010) not always in the context of kidney transplantation (Cox et al, 2005).…”
Section: Cd4mentioning
confidence: 99%
“…This renders difficult to interpret the role of thymic activity in the context of lymphopenia. In contrast, Scarsi et al [47] reported a massive reduction of RTE one year post-transplantation after Campath-1H/Alemtuzumab administration. Prolonged selective CD4 + T cell lymphopenia suggests that naive CD4 + T cells −including RTE− are highly sensitive to ATG [31,75] and that time is necessary for RTE "replenishment" after T cell depletion.…”
Section: Altered Thymic Activity a Predictive Biomarker Of Persistenmentioning
confidence: 95%
“…We imagine that these biomarkers identified in the setting of ATG can be transposed to other depleting therapies, such as Campath-1H/ Alemtuzumab. Indeed, clinical studies are available regarding the prolonged CD4 + T cell Current Issues and Future Direction in Kidney Transplantationlymphopenia induced by Alemtuzumab administration [47], not always in the context of kidney transplantation [48,49].…”
Section: Persistent Cd4 + T Cell Lymphopenia a Biomarker For Immunosmentioning
confidence: 99%